Prevalence of hypertension among healthy school going children and correlation with anthropometric indices - Gopalakrishnan, Harini; Jamalnasser, Fathima Nadia; Senthilvelan, Bharathi; Pitchairathnam, Prabu Elango (International Journal of Research in Medical Sciences, 2017)
Background: Hypertension is a major long-term health condition and is the leading cause of premature deaths among adults throughout the world. As the symptoms of childhood hypertension are largely nonspecific, children with essential hypertension are likely to be asymptomatic. The present study was designed to determine the prevalence of hypertension and prehypertension among apparently healthy school going children Methods: A total of 500 students in the age group of 10-15 years from schools were selected for the study. Height, weight and blood pressure measurements were taken. BMI was calculated using height and weight measurements. Blood pressure was classified as pre hypertension and hypertension based on systolic and diastolic blood pressure percentiles matched for age, gender and height. Results: Overall prevalence of hypertension was 11.4% and prehypertension was 23.2% in present study population. Correlation between familial history of diabetes and Ischemic heart disease and hypertensive children was found to be statistically significant (p<0.05).Among 11% of children who were found to be obese, the prevalence of hypertension (38.5%) was found to be higher than that of non-obese children (7.4%) (p<0.05). Conclusions: In conclusion, our study confirms that there is significant high prevalence of childhood hypertension. Obesity, family history of diabetes mellitus and IHD are risk factors for childhood hypertension.